(untitled) (Applied Biological Research, 2011)
The impact of vehicular pollution on foliar physiological sensitivities of two bushy ornamentals Abelia grandiflora Rehd. and Lagerstroemia indica L., growing in Srinagar (Kashmir), was assessed in year 2005 at two sites viz., Jahangir Chowk (highly polluted) and Jawahar Nagar (moderately polluted). The pollution stress significantly reduced chlorophyll a, b and total chlorophyll, N, P and K, total carbohydrate and ascorbic acid contents in plants but significantly increased proline content. Lagerstroemia indica was more vulnerable to air pollution than Abelia grandiflora.